Family Communication as a Mediator between Family Resilience and Family Functioning under the Quarantine and COVID-19 Pandemic in Arabic Countries - Aiche Sabah; Musheer A. Aljaberi; Jamel Hajji; Chuan-Yin Fang; Yu-Chen Lai; Chung-Ying Lin (MDPI AG, 2023)
The coronavirus pandemic has become an unprecedented world crisis in which we have struggled against the most potent threat of the twenty-first century. This pandemic has had a profound impact on individuals and families. Therefore, the study aimed to examine family communication as a mediator of the relationship between family resilience and family functioning under the quarantine and coronavirus pandemic in Algeria and Iraq. This study was conducted among individuals in Iraq and Algeria (N = 361). The respondents completed the Family Communication Scale (FCS), Walsh Family Resilience Questionnaire (WFRQ), and Family Functioning Scale (FFS). Structural equation modeling (SEM) with the bootstrapping method was used to conduct the mediated effects of family communication. Using the bootstrapping method in SEM, family resilience and communication significantly affected family functioning (coefficient = 0.808). Moreover, the direct effect and indirect effect (via family functioning) of family resilience on family functioning were both significant, with coefficients of 0.682 and 0.126. In addition, numerous groups from Iraq and Algeria have been analyzed as a sample and have shown no differences in the relationships between family resilience, family communication, and family functioning. In conclusion, the results showed that family communication mediated the relationship between family resilience and family functioning. Moreover, the type of this mediation seemed to be partial because of the significant direct relationship between family resilience and family functioning. According to the findings, healthcare providers should consider improving family resilience and communication to achieve good family functioning.